THE CONSUMPTION OF MILK IN CHILDREN AND IT'S RELATION TO SOCIO-ECONOMIC CONDITION - B. Bozorgmehr (Tehran University of Medical Sciences, 1979)
The purpose of this study was to investigate the possible affect of socio-economic class on the degree of acceptability and consumption of milk in children. This study was conducted on 9204 children who were chosen from two different socio-economic classes: high (groul1 1) and low (group. 2) in Tehran. Samples were aged betweea1 five to eighteen years, and divided into six age categories. The results are: The children in group used to drink milk 2-3, times more than the children in group at home. The amount of milk which was consumed by group 1 was more than group 2 (1 medium- 8 oz-glass versus 1 small- 4 oz - glass). On the other hand, group 1 consumed higher portion of the milk which was distributed at school (in. comparison to group 2). Some children refused to drink school milk. Most important reason behind refusal of school milk among group 1 seemed to be the taste of school milk, but .in group 2 this seemed to be the dislike of milk in general. Satiety which was one of the relatively important reasons for refusal of milk in group 1, was not1so, important in group 2. Clinical symptoms caused by drinking milk in group were the relatively important reason to refuse school milk, but in group 1 this was not as important. Same relation r was noticed; with respect to the students who saved the milk and: took it home after the school.